INFLUENCE OF LIGHT ON THE ANTIHEMORRHAGIC POWER OF 2-METHYL-L4-NAPHTHOQUINONE - GIRAL, FRANCISCO (My University, 1964)
A review with 14 references ABSTRACT AUTHORS: W C Tobie
CIENC MEX
Keywords: INFLUENCE, LIGHT, ANTIHEMORRHAGIC, POWER, METHYL, NAPHTHOQUINONE; MULTIDISCIPLINARIA; OTRAS ESPECIALIDADES MEDICAS (ESPECIFICAR); MEDICINA BIOQUIMICA